CLOUD TECHNOLOGIES OF OPEN SCIENCE IN THE PROCESS OF CONTINUOUS TRAINING OF ICT IN EDUCATION - Shyshkina, Mariia; Nosenko, Yuliia (Physical and Mathematical Education, 2022)
Formulation of the problem. The strategy of digital transformation of education and science is aimed at creating a single educational ecosystem that will help students and teachers to develop their digital competencies and have constant access to high-quality digital content. One of the conditions for improving the quality of training, increasing the level of professional competence of specialists regarding the wider use of innovative pedagogical technologies, and expanding the share of the research approach in education, is to ensure end-to-end ICT training in education, including due to the introduction of cloud-oriented systems of open science in institutions of higher education.Materials and methods. Analysis of research works of Ukrainian and foreign scientists, and experts, in particular scientific articles, documents, educational programs, etc.; a pilot survey of master's students (specialty 011 "Educational and pedagogical sciences", specialization "Information and communication technologies in education"), aimed at determining students' awareness of current vectors in digitalization of education and science, main modern trends, etc.Results. Realizing the need to ensure comprehensive training of specialists in digitalization of education, which involves the systematic and continuous formation of relevant competencies (including the ability to apply cloud technologies of open science) at various levels of education and is ensured by the integration of ICT training content and relevant methods, a training course was developed "Smart technologies in education". Expedient methods, forms, aids of learning, and indicative topics of content modules are proposed.Conclusions. The quality of the formation of digital competence is much higher if the conditions for the continuity of this process are ensured. An important component is acquiring the ability to apply current technologies of open science, in particular cloud-oriented systems. This can be achieved by ensuring the integration of the content of ICT education and appropriate methods, and the introduction of specialized disciplines.
Keywords: open science; cloud technologies of open science; adaptive technologies; digital competence; continuous training of ICT in education